Correlation between Reading Comprehension Skills and Students’ Performance in Mathematics - Ombra A Imam; Maripaz Abas Mastura; Hazri Jamil (International Journal of Evaluation and Research in Education (IJERE), 2013)
The deteriorating performance of Filipino students in the national and international mathematics tests for the last decade has become a major challenge to Philippine education.  The Department of Education attributed this problem to students’ poor reading comprehension. Previous studies showed varied findings on the association between variables in reading and mathematics. The present study utilized the six elements of reading comprehension skills to determine their relationship to students’ performance in mathematics. A total of 666 students belonging to the randomly selected first year classes from 18 public and private high schools were taken as sample. A correlation research design was used and a competency-based achievement tests in reading comprehension and mathematics were the research instruments. Students in private schools performed better in reading comprehension skills and mathematics than their counterparts. While reading comprehension skills were insignificantly correlated to private school students’ mathematics performance, the case is different in public schools wherein three skills namely understanding vocabulary in context, getting main idea, and making inference surfaced to have connection with mathematics. The overall students’ reading comprehension skills were not significantly correlated to mathematics performance. Hence, the poor mathematics performance could be explained by other factors not related to reading comprehension skills.DOI: http://dx.doi.org/10.11591/ijere.v2i1.1803